2004
DOI: 10.1634/stemcells.22-5-649
|View full text |Cite
|
Sign up to set email alerts
|

Human Placenta‐Derived Cells Have Mesenchymal Stem/Progenitor Cell Potential

Abstract: IntroductionMultipotential mesenchymal stem/progenitor cells (MSCs) can be induced to differentiate into bone, adipose, cartilage, muscle, and endothelium if these cells are cultured under specific permissive conditions [1,2]. In rodents, a specific type of MSC (termed multipotent adult progenitor cell) can be isolated from bone marrow (BM) and contributes to most somatic cell types when injected into early blastocysts at the single-cell level [3] , kidney, lung, and liver). These cells are also present in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
374
0
12

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 576 publications
(399 citation statements)
references
References 33 publications
13
374
0
12
Order By: Relevance
“…47 Furthermore, it has also been observed that the human placenta contains both haematopoietic stem cells and mesenchymal stem cells. 48 All tissues derived from the fetus are an extension of the mesoderm that differentiates during embryonic development to form the umbilical cord and placenta. Therefore, we further hypothesize that exposure to arsenic during fetal development could affect cellular differentiation and lineage commitment for placenta and artery but not HUVEC as this is a cellular homogenous tissue.…”
Section: Discussionmentioning
confidence: 99%
“…47 Furthermore, it has also been observed that the human placenta contains both haematopoietic stem cells and mesenchymal stem cells. 48 All tissues derived from the fetus are an extension of the mesoderm that differentiates during embryonic development to form the umbilical cord and placenta. Therefore, we further hypothesize that exposure to arsenic during fetal development could affect cellular differentiation and lineage commitment for placenta and artery but not HUVEC as this is a cellular homogenous tissue.…”
Section: Discussionmentioning
confidence: 99%
“…It was first discovered back in the mid-sixties in the bone marrow 42 then later on it was found in other different tissues such as adipose tissue, placenta and muscles. 43 1. One very important aspect of HiPSCs is that, they can be aimed to differentiate into a specified lineage which unlocked many opportunities for the research in regenerative medicine, therapeutic for disease modeling and drug discovery.…”
Section: Mesenchymal Stem Cells (Mscs)mentioning
confidence: 99%
“…S1; Supplementary Data are available online at www.liebertpub.com/scd) [9,11,21,22,29,30]. The ability of hDE-MSCs to differentiate into various myogenic lineages, however, has not been investigated.…”
Section: Hde-mscs Poorly Differentiate Toward a Cardiomyocytic Phenotypementioning
confidence: 99%
“…hDE-MSCs, as a type of MSCs, are capable of multilineage differentiation [9,11,21,22,29,30], and we sought to ascertain the specificity of MM-induced SkM differentiation in these MSCs by assaying for changes in the levels of Runx2 and PPAR-c, the master lineage transcription factors for osteogenesis and adipogenesis, respectively [40,41]. We found that in all types of hDEMSCs undergoing SkM differentiation, the expression levels of Runx2 and PPAR-c are decreased compared with undifferentiated hDE-MSCs (Supplementary Fig.…”
Section: Skm Differentiation Of Hde-mscs Was Associated With Suppressmentioning
confidence: 99%
See 1 more Smart Citation